Cohomologies p-adiques et applications arithmetiques (II) - Berthelot Pierre; Fontaine Jean-Marc; Illusie Luc; Kato K; Rapoport M (Paris Societe Mathematique de France, 2002)
This is the set of two volumes dealing with p-adic methods in arithmetic geometry. The themes appears in the 1st volume is the theory of formal groups and their deformations, the p-adic Langlands program, and the the p-adic hyperbolic geometry. The 2nd v
Keywords: Algebraic topology; Cohomology; p-adic theory